Effects of archipelago geo-environmental dynamics on phylogenetic tree shape - Amandine Vidal-Hosteng; Christophe Thébaud; Rampal S. Etienne; Robin Aguilée (Frontiers of Biogeography)
In archipelagic environments, the successive emergence and submergence of islands induces changes in area, spatial structure and isolation. Here, we aim to understand how such geo-environmental dynamics, by altering immigration, speciation and extinction over time, may influence phylogenetic patterns. We use a neutral, stochastic, individual-based model which simulates a community evolving in an archipelago where four islands emerge and submerge consecutively. We record each birth, death and immigration event, allowing us to build the complete phylogeny at any time, from which we extract the phylogeny of extant species. We show that the rate of lineage accumulation and tree imbalance vary according to a hump-shaped curve, and we show that this is mainly due to variations in area and inter-island connectivity. We highlight that past abrupt changes, such as island emergence, may leave persistent imprints in the rate of lineage accumulation. We show that the spatial configuration of an archipelago modulates these effects: (i) enhancing inter-island connectivity leads to more frequent inter-island speciation events, resulting in a faster accumulation of lineages, and in larger evolutionary radiations, which in turn produce highly imbalanced phylogenies; (ii) increase in mainland connectivity brings ancestral lineages to the islands, which slows down the rate of lineage accumulation and increases the species turnover, allowing for more balanced phylogenies. Accounting for variations in the geo-environmental configuration of an archipelago is important to understand the shape of contemporary phylogenies. However, these effects have to be interpreted in the context of the spatial configuration of an archipelago. Highlights The emergence and submergence of islands in an archipelago influences immigration, speciation and extinction rates at both island and archipelago scales Landscape dynamics in an archipelago drives insular species diversification rates and influences phylogenies of island species Inter-island dispersal favors lineage accumulation and generates imbalanced phylogenies Mainland connectivity increases species turnover, slows down lineage accumulation and makes phylogenies more balanced The establishment and size of a phylogenetic island clade may depend on the spatial configuration of the archipelago at the time of colonization